Successful reintroduction of methotrexate after pneumonitis in two patients with rheumatoid arthritis. - Cook, N J (1992)
Two patients are described with severe and progressive rheumatoid arthritis in whom methotrexate was reintroduced despite previous methotrexate related pneumonitis. In both patients a marked improvement in disease control occurred without a recurrence of the pneumonitis.